PHENOTYPES OF POLYCYSTIC OVARY SYNDROME AND ACCOMPANYING HORMONAL DISTURBANCES - Karatas, Savas; Hacıoglu, Burcu; Kalayci, Gokhan (Sanamed, 2022)
Objective: PCOS, which is known as a symptom complex including menstrual dysfunction (OD) and or hirsutism/androgen excess (HA),  and/or polycystic ovaries (PCOM), induces women's health damage beyond this classical criteria. Subphenotypes of PCOS have different clinical properties and criteria, and the metabolical differences between these phenotypes have not been elucidated properly. Therefore, we aimed to investigate the metabolic and endocrinological differences between these sub-phenotypes.Materials and Methods: 63 patients with PCOS  followed by Istanbul Research and Education Hospital Endocrinology and Metabolism Department were included in the study. Patients were classified into subgroups according to phenotypes. The phenotype groups were compared according to blood glucose, lipid parameters, and serum hormone levels. MetS ratios between groups were also compared.Results: Androgen excess/hirsutism was the most prominent character with a 95.2% (n=60) rate in this study group, and ovulatory dysfunction was the least prominent one. (n=43, 68.2%) PCOM has been detected in 50 patients (80.8%). Patients were grouped according to PCOS phenotypes. Phenotype C was the most common type, and about 65% of the patients were in this group. Triglyceride levels were statistically significantly higher in the Phenotype A group than in the Phenotype B group (p=0.03). MetS was the highest in the Phenotype A group (45.4%) and the lowest in the Phenotype C group (34.7%).Conclusions: Phenotype C has the highest prevalence in Turkish patients with PCOS, MetS was the highest in Phenotype A, and TG and LDL cholesterol levels were higher in Phenotype A.  More studies are needed to explain these differences and their lifetime consequences.
Keywords: polycystic ovary syndrome; metabolic syndrome; hirsutismus; hyperlipidemia; androgens